Hubungan Pengetahuan dan Sikap Dengan Kepatuhan Minum Obat Anti Diabetes Pada Pasien Diabetes Melitus di Puskesmas PB Selayang II - Selfianna Rosalina Br Ginting (Journal of Pharmaceutical and Sciences, 2023)
Hyperglycemia as a result of abnormal insulin secretion is a hallmark of diabetes mellitus, a metabolic condition, the objective of this study was to ascertain the connection between knowledge, attitudes, and medication adherence. The kind of exploration utilized by specialists is insightful observational examination with a cross-sectional exploration plan. The majority of people with diabetes mellitus were between the ages of 61 and 70, had mostly completed high school (up to 100, or 46.5%), worked as farmers (up to 79, or 36.7%), and were women (up to 108, or 50.2%). Knowledge was mostly negative (78.1%), attitudes were mostly disagreeable (79.1%), and compliance was mostly disobedient (72.1%), according to the study's findings. The chi square statistical test revealed p values of 0.039 for knowledge and 0.024 for attitude. This demonstrates that the p-value is less than or equal to 0.05. From that point, it tends to be inferred that there is a connection between information, mentalities and consistence at the PB Selayang II Wellbeing Community